Effect of the Copaifera langsdorffii Desf. Leaf Extract on the Ethylene Glycol-Induced Nephrolithiasis in Rats - de Oliveira, Rejane Barbosa (Hindawi Publishing Corporation, 2013)
The potential of the Copaifera langsdorffii leaves extract to prevent stone formation was analyzed by means of an ethylene glycol (EG) animal model of nephrolithiasis and an in vitro crystallization assay. Different doses of the C. langsdorffii leaves extract were administered to rats treated with EG. Urine biochemical parameters were quantified. CaOx deposits count and analysis of osteopontin expression were conducted on kidneys fixed in formalin. The in vitro assay was performed by turbidimetry. Phytochemical analyses of the extract were accomplished by HPLC-UV-DAD, and several compounds were isolated. C. langsdorffii leaf extract was able to avoid stone formation. The number of deposits was 50.30 ± 31.29 at the higher extract dose, compared to the value of 179.5 ± 45.96 achieved with the EG control. Significantly lower oxalate levels and OPN expression and increased citrate levels were observed after extract administration. In the in vitro assay, the extract diluted the formed crystals. Phytochemical analyses showed that the extract is rich in phenolic compounds that are capable of preventing stone formation. Thus, on the basis of our results, we suggest that the C. langsdorffii leaf extract has potential application in the prevention of kidney stone formation.